10-Year Study of Christian Church Support for Domestic Violence Victims: 2005-2015 - Duie-Züst, Barbara (Journal of interpersonal violence, 2021)
Religious beliefs play a significant role in the lives of victims of domestic violence. Victims find strength in their faith and would rather endure the violence at all costs to keep a family or a marriage together, than to compromise their faith by leaving.Purpose:This 10 –year study explored the climate of support for victims of domestic violence among Christian clergy and church members between 2005 and 2015.Method:Using a convenience sample, surveys were sent out to congregations in the Upper Midwest in 2005 and 2015. The survey included demographics; two items measuring perception of domestic violence in the congregation andcommunity; six Likert Scale items regarding agreement with statements concerning leaving an abusive marriage; four ‘Yes-No’ items regarding the impact of faith in leaving, support of the congregation, community resources,and clergy as counselors. The clergy’s survey had the same questions, plus open-ended questions about their skills in counseling victims, their congregation’s support for victims, community resources, and beliefs that could impact a victim’s choice in leaving.Analysis:Data were analyzed using descriptive statistics, simple frequencies, and bivariate correlations. Narrative data were analyzed using content analysis.Results:The results of this study indicated that change is slow. Members want their clergy to become more educated in counseling and in speaking about domestic violence from the pulpit. Clergy felt comfortable in making referrals for professional counseling, while the majority of members would prefer counseling with their pastor if they were in a violent relationship. Both clergy and members want to create a safe and supportive environment for victims/survivors of violent relationships. Findings from this study exemplify the need for pastors to remove the silence about domestic violence in their congregations and address the misunderstood social religious beliefs that may bind a victim to the violence.